Isolated Unilateral Strabismus Sursoadductorius (Congenital Trochlear Palsy) with and without Hypotrophia of the Superior Oblique Muscle-Orthoptic Differences in Adulthood - Gusek-Schneider, Gabriele-Charlotte; Kaestle, Nicola; Reil, Franziska; Schuerhoff, Sabine; Engelhorn, Tobias (Klinische Monatsblätter für Augenheilkunde, 2018)
PURPOSE: The clinical feature of unilateral decompensating strabismus sursoadductorius (dSSA; often called congenital superior oblique palsy, CSOP) is not an etiologically uniform entity. Hypotrophy of the superior oblique muscle (HMOS) is a frequent and immediate cause of dSSA/CSOP. In this study, clinical characteristics of dSSA/CSOP with and without HMOS are compared. PATIENTS AND METHODS: Twenty-five consecutive patients (age 14 - 69 years; median 43 years) were included in this study, 14 with 3T MRI-proven HMOS (group 1) and 11 without HMOS (group 2). HMOS was defined as a reduction of the medio-lateral (ML) as well as based on ML and cranio-caudal (CC) diameter calculated area = (ML · CC/4) · π of the affected superior oblique muscle (SOM) < 80% in comparison to the contralateral SOM (measured on the single coronal image on which the muscle has its greatest extent). The two groups were compared in terms of head tilt, cyclo- and vertical deviation and the Bielschowsky head tilt test. Patients were classified according the Knapp's classification. RESULTS: Both the incidence of head tilt with 14/14 vs. 5/11 (χ2 = 0.003) and its degree: 11.1 ± 4.5° vs. 3.2 ± 4.1° (p < 0.001) was higher in group 1 than in group 2, as well as the Bielschowsky head tilt test: 9.3 ± 4.3° vs. 3.8 ± 4.9° (p = 0.008). The average amount of hypertropia was larger in group 1 than in group 2 during adduction: 16.7 ± 5.3° vs. 9.3 ± 3.4° (p < 0.001) as well as during adduction and downgaze of the affected eye: 14.6 ± 7.1 vs. 7.2 ± 3.7° (p = 0.03). In the sagittal plane, the increase of vertical deviation was larger in group 1 than in group 2: 2.8 ± 7.8 vs. - 2.4 ± 4.2 (p = 0.04); the excyclodeviation was larger in group 1 in all three planes (sagittal plane, adduction and abduction) in comparison to group 2: 1.3 ± 4.1 vs. - 2.9 ± 2.8 (p = 0.006), 2.4 ± 5.2 vs. - 2.2 ± 2.9 (p = 0.01), 0.5 ± 3.8 vs. - 2.7 ± 3.9 (p = 0.05). Knapp's class II was found in 6 of 15 patients in group 1 and only in this patient group (χ2 = 0.03). CONCLUSIONS: In both groups, the vertical deviation showed a great dispersion. In patients without HMOS (group 2), vertical deviation in adduction did not exceed 15°. Patients with HMOS (group 1) do not show the typical features of a later acquired trochlear palsy due to an early developed compensating innervation. A vertical deviation in adduction of more than 15°, increasing excyclodeviation towards downgaze in all three planes (sagittal plane, adduction and abduction) and Knapp's class II are relatively reliable predictors of a hypoplasia of the SOM. An internationally uniform term for this group of patients, such as superior oblique weakness or superior oblique hypotrophy, would be desirable.
EVALuna2:34915